Gefährden institutionelle Anleger den Wettbewerb? - Achim Wambach; John P. Weche (Wirtschaftsdienst, 2016)
Die Monopolkommission kommt in ihrem aktuellen Gutachten zu dem Ergebnis, dass indirekte Horizontalverflechtungen zwischen Unternehmen desselben Marktes über institutionelle Investoren ein wettbewerbsverzerrendes Potenzial bilden. Durch Minderheitsbeteiligungen institutioneller Anleger an mehreren Anbietern einer Branche könne das Interesse an der Gesamtmarktrendite im Vordergrund stehen, was die Anreize zu wettbewerblichem Verhalten abschwächt. – – The Monopolies Commission, which advises the German government in competition policy making, warns against potential anti competitive effects of indirect horizontal links between competitors via institutional investors. Through such common ownership, the competitive conduct between suppliers could be alleviated, because their (joint) institutional shareholders interest in the overall market return may outweigh their interest in the individual fi rms' returns. Taking account of the ubiquity of such common ownership in European and global markets as well as a non consideration in current competition law, the Monopolies Commission's call for more research and vigilance appears to be appropriate.
Keywords: G34; L10; L41; 330